Defensive Strategy Analysis of Bag Handicraft Industry in SME Centers - Yusuf*, Ramayani; Veranita, Mira; Gunardi, Gunardi; Oktaroza, Magnaz Lestira; Cupiadi, Hedi (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2024)
With the rapid development of technology, various problems arise in producing and marketing handicraft products. Thus, this research aims to determine the survival strategies and provide a clear and detailed picture of the characteristics or attributes of research subjects without testing hypotheses or drawing causal conclusions. The research object is the bag craftsmens in Sukaregang, Garut Regency West Java, Indonesia. Both interview techniques and literacy studies were used to obtain the strengths, weaknesses, opportunities, and threats. Then, weighting is carried out, and a value is given; the weight and value are multiplied to get a total score. The existing IFAS and EFAS values are entered into quadrants. It is found that the position of Sukaregang bag craftsmen is in quadrant 1 which aims to take advantage of internal strengths and external opportunities. The strategy that can be applied is to improve the quality of raw materials so that they can produce good, high-quality, and high-value products. These findings are expected to provide insights for handicrafts to survive this digital era. Keywords: Economy; Management; Defensive Strategy; SWOT; SMEs